2011
DOI: 10.1111/j.1467-6451.2011.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

LICENSE AUCTIONS WHEN WINNING BIDS ARE FINANCED THROUGH DEBT*

Abstract: We study an auction where two licenses to operate on a new market are sold and winning bidders finance their bids on the debt market. Higher bids imply higher debts which affects product market competition. When debt induces firms to compete more aggressively, retail prices are lower than in a model without debt, as are auction revenues. When debt induces firms to compete less aggressively, retail prices are higher than in a model without debt, and the effect on auction revenues is ambiguous. Net firm profits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…But Cave and Valetti (2000) have shown that the spectrum auction through ascending auction need not necessarily be bad as the license fee is only a sunk cost. Haan and Toolsema (2003) show that consumers' price may be lower under spectrum auction than under beauty contests. On the other hand, Burguet (2005) shows how the beauty contest method is a better approach to spectrum distribution than the auction of licensing.…”
Section: Literature Reviewmentioning
confidence: 95%
“…But Cave and Valetti (2000) have shown that the spectrum auction through ascending auction need not necessarily be bad as the license fee is only a sunk cost. Haan and Toolsema (2003) show that consumers' price may be lower under spectrum auction than under beauty contests. On the other hand, Burguet (2005) shows how the beauty contest method is a better approach to spectrum distribution than the auction of licensing.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Janssen and Karamychev (2009) show that less riskaverse bidders are more likely to win auctions and to price their products higher post-auction. Haan and Toolsema (2011) show that where bidders finance their bids through the debt market, debt levels may affect post-auction pricing. Studying 47 countries, Kuroda and del Pilar Baquero Forero (2017) find that penetration rates are lower in countries that conduct auctions.…”
Section: Spectrum License Feesmentioning
confidence: 99%
“…According to Janssen and Karamychev (2009), telecommunication companies that are not overly risky as auction bidders tend to win the auction and price their products higher afterward. According to Haan and Toolsema (2011), the level of debt influences post-auction consumer prices for the bidder who wins the auction with debt financing. Kuroda and Forero (2017) discovered a lower penetration rate in auction countries after studying 47 countries.…”
Section: Introductionmentioning
confidence: 99%